Economic Autonomy of Latin American Women - Medina Hernández, Edith Johana; Fernández Gómez, María José (Universidad Pedagógica y Tecnológica de Colombia, 2021)
Access to paid work, the occupation according to productivity sectors and the time use are factors that influence the ability of women to generate their own income, therefore, they conditionate the economic autonomy and should be presented on equal terms with respect to men. The main objective of this research is to know the labor position of Latin American women through the analysis of 6 employment indicators in 15 countries of the region, which were compiled and published in 2020 by the Gender Observatory of the Economic Commission for Latin America and the Caribbean (ECLAC). Through the HJ-Biplot multivariate technique, similarities and differences between indicators, countries and genders were explored, to find out the conditions that do not favor the economic empowerment of women or their participation in the labor market. It is concluded that the Central American nations register the largest gaps in economic autonomy both between men and women in Latin America, while in countries such as Uruguay, Colombia, Costa Rica, Chile, Panama and Brazil, there are increased opportunities for female employment in high productivity sectors.